(untitled) (Journal of Advanced Veterinary and Animal Research, 2015)
This case report describes the necropsy findings of two potentially zoonotic parasites infecting the Philippine brown deer (Cervus mariannus) in Leyte Island, Philippines. A female deer aging approximately 5-year was presented for necropsy to the Diagnostic Laboratory at the College of Veterinary Medicine, Visayas State University. Gross pathology was recorded and the selected organs having lesion were collected for histopathological studies. Results showed severe necrotizing lesions in the nasal and palatal areas, infestation of calliphorid maggots, hepatic fibrosis, cholangitis, cholecystitis, lung atelectasis and duodenitis. Heavy ruminal fluke infection was also observed. Two potentially zoonotic parasites namely Fasciola gigantica and Sarcocystis spp. were identified. The Philippine brown deer appears to have a role in transmission and amplification of zoonotic parasites, and can also be threatened by diseases caused by the parasites. http://dx.doi.org/10.5455/javar.2015.b110